(3Pjd Sdc GdOQQs - (3eMeO Ndjd Hf Ydj GdeQGOj GdOeTbj,J (B1206 (3g` s
(3ChdgG (B:s
(3jHOC HGSeGYjd Hf eMeO Hf UGdM GdMdHi GdSgjQ HGdehGgHi s
(3BNQgG (B:s
(3jfJgi HWg Hf eMeO Hf Wg Hf CMeO GdYbGO GdMdHi GdTGaYi s
(3fSNI UhQJ HGdbGgQI SfI (B1346 (3ef fSNI GdaGVd GdSjO MSGe GdOjf GdbOSi GdOeTbi hGdXGgQ CfgG eShOI GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B118s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B138 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdJjehQjI (B((3JGQjN (B2409) s
Keywords: (3GdJGQjNs